Identification of Phytocyanin Gene Family in Legume Plants and their Involvement in Nodulation of Medicago truncatula. (15th January 2019) - Sun, Yali; Wu, Zefeng; Wang, Yujie; Yang, Jieyu; Wei, Gehong; Chou, Minxia
Abstract: The establishment of symbiosis between legume and rhizobium results in the formation of nodule. Phytocyanins (PCs) are a class of plant-specific blue copper proteins, playing critical roles in plant development including nodule formation. Although a few PC genes have been isolated from nodules, their functions are still unclear. Here, we performed a genome-wide identification of PC family in seven sequenced legume species ( Medicago truncatula, Glycine max, Cicer arietinum, Cajanus cajan, Lotus japonicus, Vigna angularis and Phaseolus vulgaris ) and found PCs experienced a remarkable expansion in M. truncatula and G. max . Further, we conducted an in-depth analysis of PC family in the model legume M. truncatula . Briefly, 82 MtPCs were divided into four subfamilies and clustered into seven clades, with a large proportion of tandem duplications and various cross-tissues expression patterns. Importantly, some PC s, such as MtPLC1, MtENODL27 and MtENODL28 were preferentially expressed in nodules. Further, RNA interference (RNAi) experiment revealed the knockdown of MtENDOL27 and MtENDOL28 impaired rhizobia infection, nodule numbers and nitrogenase activity. Moreover, in the MtENODL27 -RNAi nodules, the infected cells were reduced and the symbiosomes did not reach the elongated stage, indicating MtENDOL27 is required for rhizobia infection and nodule development. In addition, co-expression analysis showed MtPLC1, MtENODL27 and MtENODL28 were grouped into two different functional modules and co-expressed with the known symbiotic nitrogen fixation-related genes, suggesting that they might participate in nodulation via different ways. In summary, this study provides a useful resource for future researches on the structure and function of PC s in nodulation.